CLINICAL AND ECONOMIC ANALYSIS OF USING OF LONG ACTION ERYTHROPOES STIMULATED AGENTS FOR THE TREATMENT OF ANEMIA CKD V HD PATIENTS - M. Kolesnyk; N. Bezdetko; V. Novakivskyy (Український Журнал Нефрології та Діалізу, 2015)
The article describes the ways to cost optimization of anemia treatment CKD - HD patients.